Education for Sustainable Development (ESD) in Post-modernity: A Case Study of Japanese Value Manifestation in Vocational Education in Greater Mekong Sub-Region Country - Juwitasari, Reni (Journal of Technical Education and Training, 2024)
Realists believe vocational education and training (VET) serves global economic-oriented goals. Consequently, a Perennialism-based curriculum is implemented to emphasize market-relevant skills. However, in the Greater Mekong Sub-Region (GMS), the reality of vocational education falls short of promoting skilled labor and requires improvement. Since its establishment in 1992, major power countries like Japan played a crucial role after the Second World War by adopting a prominent foreign policy of official development assistance (ODA) to enhance Human Resource Development (HRD) for the region’s economic development. As part of its ODA strategies, Japan has assisted VET in the region while simultaneously promoting its own value of Kaizen under its system of KOSEN to improve HRD with green skills. This research explores Kaizen’s value in Education for Sustainable Development (ESD), specifically in Thailand and Vietnam's Mekong emerging economic powers. The study seeks to promote knowledge, situational awareness, and cultural relativism in developing meaningful green skills by considering a 3-pillar of environment, socio-culture, and economy within a postmodernist framework. The research employed a qualitative approach and semi-structured interviews. Four respondents from Thai and Vietnamese institutions were selected using purposive sampling techniques. The findings revealed that the pragmatic implementation of Kaizen in Thai and Vietnamese VET had fostered green skills and environmental awareness influenced by a constructive culture. Importantly, the postmodernist-based curriculum provides a platform for diverse perspectives, challenging the absolute Western global agenda claim and advocating for the decolonization of local values through a concept known as Cosmo-localism, which aligns with the foundation Kaizen since the 1950s.